Fabrication of Y-junction Metal Nanowires by AAO Template-assisted AC Electrodeposition - Duan, Huanan; Xia, Zhenhai; Liang, Jianyu (Nano-Micro Letters, 2011)
In this communication, we report a synthetic approach to fabricate Y-junction Co nanowires and Y-junction Cu nanowires by AC electrodeposition using a hierarchically designed anodized aluminum oxide template. Morphology study showe that diameters of the stems and branches of the Y-junction nanowires were about 40 nm and 20 nm respectively. Structural analysis indicates that Co nanowires had a mixture of face-center-cubic and hexagonal-close-packed structures, whereas Cu nanowires had a face-center-cubic structure with a <110> texture. The Y-junction Co nanowires exhibited a longitudinal coercivity of 1300 Oe and remnant magnetization of 56%, which was affected by the growth direction and microstructure. The present method can be extended to other metallic systems and thus provides a simple and efficient way to fabricate Y-junction metal nanowires.